A prospective study of direct‐acting antiviral effectiveness and relapse risk in HCV cryoglobulinemic vasculitis by the Italian PITER cohort. Issue 1 (19th January 2022) - Kondili, Loreta A.; Monti, Monica; Quaranta, Maria Giovanna; Gragnani, Laura; Panetta, Valentina; Brancaccio, Giuseppina; Mazzaro, Cesare; Persico, Marcello; Masarone, Mario; Gentile, Ivan; Andreone, Pietro; Madonia, Salvatore; et al.
Abstract: Background and Aims: Mixed cryoglobulinemia is the most common HCV extrahepatic manifestation. We aimed to prospectively evaluate the cryoglobulinemic vasculitis (CV) clinical profile after a sustained virologic response (SVR) over a medium‐term to long‐term period. Approach and Results: Direct‐acting antiviral–treated cryoglobulinemic patients, consecutively enrolled in the multicentric Italian Platform for the Study of Viral Hepatitis Therapy cohort, were prospectively evaluated. Cumulative incidence Kaplan‐Meier curves were reported for response, clinical deterioration, relapse and relapse‐free survival rates. Cox regression analysis evaluated factors associated with different outcomes. A clinical response was reported in at least one follow‐up point for 373 of 423 (88%) patients with CV who achieved SVR. Clinical response increased over time with a 76% improvement rate at month 12 after the end of treatment. A full complete response (FCR) was reached by 164 (38.8%) patients in at least one follow‐up point. CV clinical response fluctuated, with some deterioration of the initial response in 49.6% of patients (median time of deterioration, 19 months). In patients who achieved FCR and had an available follow‐up (137 patients) a relapse was observed in 13% and it was transient in 66.7% of patients. The rate of patients without any deterioration was 58% and 41% at 12 and 24 months, respectively. After achieving SVR, a clinical nonresponse was associated with older age and renal involvement; a clinical deterioration/relapse was associated with high pretreatment rheumatoid factor values, and FCR was inversely associated with age, neuropathy, and high cryocrit levels. Conclusion: In patients with CV, HCV eradication may not correspond to a persistent clinical improvement, and clinical response may fluctuate. This implies an attentive approach to post‐SVR evaluation through prognostic factors and tailored treatment. Abstract : image